Secretory vesicle trafficking in awake and anaesthetized mice: differential speeds in axons versus synapses - Knabbe, Johannes; Nassal, Joris; Kuner, Thomas (The journal of physiology, 2018)
Our work provides a basis to extrapolate DCV transport properties determined in cultured neurons to the intact mouse brain and reveals novel features such as slowing upon bouton approach and brain state‐dependent trafficking directionality.